Evidence and conjecture about mechanisms of cutaneous disease in photodermatology. Issue 8 (August 2014) - Porter, Rebecca M.; Anstey, Alex
Abstract Photosensitivity disorders are caused by a variety of mechanisms. Three common themes are as follows: excess chromophore allowing visible light energy to cause photodynamic damage, reduced DNA repair capacity to UV‐induced DNA damage, and enhanced sensitivity to light‐induced allergens mediated immunologically. Although the cause of each condition may be known, the precise pathogenesis underlying the photosensitivity has taken longer to understand. By focussing on three clinical disorders under each of these themes, we have explored the following: why erythropoietic protoporphyria differs so markedly from the other cutaneous porphyrias; how a DNA repair defect was eventually revealed to be the underlying cause of the vitamin B3 deficiency disorder of pellagra; an immunological explanation for the over reactivity to photoallergens in chronic actinic dermatitis.